Winter Wheat Row Spacing and Alternative Crop Effects on Relay-Intercrop, Double-Crop, and Wheat Yields - Leah Sandler; Kelly A. Nelson; Christopher Dudenhoeffer (International Journal of Agronomy)
In Missouri as well as much of the Midwest, the most popular double-cropping system was winter wheat (Triticum aestivum L.) followed by soybean (Glycine max (L.) Merr). These two crops can also be used in an intercrop system, but optimal row spacing was important to increase crop productivity. Research was conducted to evaluate (1) winter wheat inter- and double-crop production systems, using a variety of alternative crops, and (2) the impact of different wheat row spacings on intercrop establishment and yields within the various cropping systems. Field research was conducted during droughts in 2012 and 2013. Spacing of wheat rows impacted wheat yields by 150 kg ha−1, as well as yields of the alternative crops. Narrower row spacings (150 kg ha−1) and the double-crop system (575 kg ha−1) increased yield due to the lack of interference for resources with wheat in 2013. Land equivalent ratio (LER) values determining productivity of intercrop systems of 19 and 38 cm row showed an advantage for alternative crops in 2013, but not 2012. This signified that farmers in Northeast Missouri could potentially boost yield potential for a given field and produce additional forage or green manure yields in a year with less severe drought.